Pengaruh Pola Asuh Otoriter, Autoritatif, Permisif Orang Tua Terhadap Perilaku Prososial Siswa Sekolah Dasar - Titin Prastyawati; Sudi Dul Aji; Joice Soraya (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2021)
The problems formulated in the study are as follows: 1) Is there an influence of authoritarian parenting on students' prosocial behavior ?, 2) Is there an influence of authoritative parenting on students' prosocial behavior ?, 3) Is there an effect of permissive parenting on students' prosocial behavior? , 4) Is there an influence of authoritarian parenting, authoritative, and permissive together on the prosocial behavior of students of Elementry School? This research is a survey research with a quantitative approach that is non-experimental, with a correlational method. The sampling technique used is probability sampling. By using a simple random sample which is a sampling technique that provides equal opportunities to every member in a population to be sampled. The sample population of this study were students in grades IV, V, and VI of SD Negeri 5 Lawang, Lawang District, Malang Regency, which totaled 105 students in the 2019/2020 school year. Content validity test uses a reliability test with internal consistency using Cronbach's Alpha. The data analysis technique used is multiple regression analysis. The results showed 1) there was a positive influence of authoritarian parenting on prosocial behavior with a contribution of R2 of 0.432 or 43.2%, regression equation Y = 56.48 + 0.141 X1, 2) there was a positive influence of authoritarian parenting on prosocial behavior with contributions R2 value of 0.432 or 43.2%, regression equation Y = 56.48 + 0.619 X2, 3) there is a positive effect of authoritarian parenting on prosocial behavior with a contribution of R2 of 0.432 or 43.2%, regression equation Y = 56, 48 + 0.391 X3. The meaning of the results of the study is the influence of strong parenting on prosocial behavior is authoritative parenting